Preparation of fine-grain lead indium niobate ceramics with wolframite precursor method and resulting electrical properties - Yimnirun R. (2014)
In this study, lead indium niobate (Pb(In1/2Nb 1/2)O3 or PIN) ceramics were prepared by a wolframite precursor method via a vibro-milling technique. Fine-grain ceramics were achieved with average grain size of 1-2 μm, indicating advantage of the vibro-milling technique used. The dielectric and ferroelectric properties were measured by means of an automated dielectric measurement set-up and a standardized ferroelectric tester, respectively. The dielectric properties of PIN ceramic were measured as functions of both temperature and frequency. The results indicated that the dielectric properties of the PIN ceramic were of relaxor ferroelectric behavior with temperature of dielectric maximum (T m) ∼ 53 °C and dielectric constant (εr) ∼ 4300 (at 1 kHz). The P-E hysteresis loop measurements at various temperatures showed that the ferroelectric properties of the PIN ceramic changed from the paraelectric behavior at temperature above Tm to slim-loop type relaxor behavior at temperature slightly below Tm. Moreover, the P-E loop became more open at temperatures much lower than Tm. © Springer-Verlag 2007.